Want power? The Lackof condom Usein reports of young Women - Ribeiro, Karla Carolina S; Silva, Josevânia da; Saldanha, Ana Alayde W (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: the socio-historical constructions of gender constitute an obstacle to the negotiation of condom use by women, by prioritizing the maternal and procreation focus, opposing the proposal for prevention. Objective: to analyze vulnerability to STD and unplanned pregnancy in female adolescents. Methods: it was a field of study, which surveyed 8,471 adolescents, of whom 62% were females, with a mean age of 16.6 years old. We used a structured self-administered questionnaire and discussion groups.The first instrument was analyzed using descriptive statistics and the second through the categorical analysis. Results: regarding the sexual practice, 31% of participants report having active sexual life, with initiation of 15.6 years for females and 14.6 years for males. The lack of condoms at first intercourse was reported by 35% of men and 39% of women, while 21% of men and 43% of women did not use it at their last sexual intercourse. Among the explanations given in the discussion groups, we highlight the inexperience, the existence of negative beliefs, the unpredictability of the act, the difficulty of obtaining the condom, lack of information and type of bonding. Conclusion: there is greater difficulty for women in the use of preventive practices due to the maintenance of historically constructed beliefs that place them in situation of subjective dependence, leading to situations of greater vulnerability. Actions in the communities, and focused networks emotional-sexual relationships, may prove a more effective approach to reduce the risk of infection with DST/aids and unplanned pregnancy in adolescents.